Unemployment and Productivity in the Long Run: The Role of Macroeconomic Volatility - Benigno, Pierpaolo; Ricci, Luca Antonio; Surico, Paolo (The Review of Economics and Statistics, 2015)
This paper presents a new empirical regularity between the volatility of productivity growth and long-run unemployment for a given level of long-run productivity growth. A theoretical framework based on asymmetric real wage rigidities is shown to have the potential to rationalize this finding. The model tends to fit U.S. long-run unemployment better than a specification based on long-run productivity growth only, especially during the Great Moderation and the Great Recession.